Penguatan Kompetensi Guru melalui Implementasi Design Thinking untuk Mendukung Pembelajaran Mendalam di SMP Kota Pekalongan - Fenny Roshayanti; Nizaruddin Nizaruddin; Muhammad Syaipul Hayat; Sumarno Sumarno (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
The implementation of the Merdeka Curriculum requires learning practices that foster deep learning, which teachers are expected not only to deliver content but also to cultivate higher-order thinking skills and design instruction that accommodates diverse student characteristics. However, observations and interviews at SMP Negeri 12 Pekalongan revealed that teachers still face limitations in planning and managing adaptive learning. Their understanding of students’ interests and needs remains at a general diagnostic level, making it difficult to fully address individual differences in potential and character. To address this challenge, a Community Service program was carried out through training and mentoring in the application of design thinking as a creative, problem-solving–oriented approach. The program consisted of five main stages: socialization, workshop and training, technical training and implementation, program evaluation, and program continuity. The training combined 25% theory and 75% practice using case studies, simulations, and interactive discussions to provide teachers with hands-on experience in designing design thinking–based learning materials. Mentoring sessions ensured that teachers could implement the concept in classroom practice. Evaluation results showed that 85% of participating teachers understood the concept of design thinking and were able to apply it in heterogeneous classrooms, with the majority successfully developing learning tools ready for classroom implementation. These findings demonstrate that design thinking training and mentoring effectively enhance teachers’ capacity to design creative, adaptive, and student-centered instruction, while also supporting the realization of deep learning in schools.